Comparison of Intervention Programs to Improve Trunk Stability for Active Females - Kate Schwartzkopf-Phifer; Katie Whetstone; Mark Marchino; Kevin Brown; Kyle Matsel (North American Sports Medicine Institute, 2023)
# Background Current literature illustrates a disparity in trunk stability push up performance (TSPU), as measured by the Functional Movement Screen (FMSTM), in females throughout the lifespan when compared to their male counterparts. # Hypothesis/Purpose The purpose of this study was to evaluate the effectiveness of a novel exercise approach to a trunk stability (NEATS) program compared to a standard Pilates program on TSPU performance in active females aged 18-45 years. It was hypothesized that subjects in the NEATS program would have greater improvements on outcomes related to trunk stability than subjects in the Pilates program. # Study Design Randomized controlled trial # Methods All subjects were tested at baseline on Beighton criteria, the FMSTM, Y-Balance Test Upper Quarter and Lower Quarter, and grip strength by an evaluator blinded to group allocation. Subjects were randomized into the NEATS (n=17) or the Pilates group (n=19). The intervention period lasted eight weeks, with exercise progression at weeks two, four, and six. # Results The main outcome was between-group pass rates on the TSPU. At posttest, 41% (n=7) of the NEATS group and 42% (n=8) of the Pilates group passed the TSPU, though there was no difference between groups (p=0.97). Significant differences were noted on the TSPU (Pilates, NEATS p=0.01) and composite scores (Pilates p=0.01; NEATS p=0.03). No within-group improvements were noted on the individual scores of the FMSTM (p=0.05-0.66). Within-group differences were noted on the posterolateral reach on the Y-Balance Test Lower Quarter (p=0.03) in the Pilates group. Between-group posttest continuous measures were not significantly different (p=0.17-0.96). # Conclusion Improvements in trunk stability were comparable between the multi-planar NEATS program and a standard Pilates program suggesting that both can be used to improve trunk stability performance in active females. # Level of Evidence 2